Post-Materialism and Political Grievances: Implications for Protest Participation in Hong Kong. (February 2023) - Charm, Theodore; Lin, Tse-min
In recent decades, Hong Kong witnessed a number of protest movements that drew high levels of participation, most of which revolved around political issues. Why did ordinary citizens protest? What were the underlying factors that motivated Hongkongers to protest? We argue that post-materialism and grievances toward the government increase the selective expressive benefits for individuals to participate in protests. We illustrate that the two factors contribute to the protest movements in Hong Kong in general. Using the World Values Survey data, we found that post-materialism interacted with grievances toward the political system to increase Hongkongers' propensity to protest. Our findings have important implications for the 2019 Anti-Extradition Law Movement in Hong Kong.